The Legal Implications of Bankruptcy on the Joint Property of Spouses Without a Prenuptial Agreement - Fania Putri Pradana; Dominikus Rato; Moh. Ali (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2026)
Marriage as a legal institution not only gives rise to a personal relationship between husband and wife, but also produces significant legal consequences for the status of property. Within the Indonesian positive-law system, the regulation of marital property is a crucial aspect, particularly when a legal event in the form of the bankruptcy of one of the parties to the marriage occurs. The problem becomes even more complex where the marriage is contracted without a prenuptial agreement governing the separation of property. This study aims to analyse the legal regulation of marital property under positive law in Indonesia and to examine the legal implications for marital property in the event of the bankruptcy of a husband or wife in the absence of a prenuptial agreement. The research method employed is normative juridical, using a statute approach and a conceptual approach. The statute approach is carried out through an examination of the Marriage Law, the Civil Code, and the Bankruptcy and Suspension of Payment (PKPU) Law, while the conceptual approach is used to examine the principles, doctrines, and legal concepts relating to joint property and bankruptcy. The results show that in marriages without a prenuptial agreement the principle of community of property applies, so that property acquired during the marriage is qualified as joint property. If one of the parties is declared bankrupt, the joint property is in principle absorbed into the bankruptcy estate (boedel pailit) and administered by the curator for the benefit of the creditors. Nevertheless, the law continues to protect brought-in property (harta bawaan) and personal property acquired through gift or inheritance. This study affirms the importance of understanding and regulating marital property as a preventive measure to minimise the legal risks arising from bankruptcy in a marriage.